(untitled) (Medico Legal Update, 2020)
Vaccines are important factors in the health system , and more benefit for the health and develops population, the study was conducted among chidden with age between one month to three yeas old age for period 4 months from April to July 2018 , were data collection among mothers (N=300) attending primary health care center in Al-Noor City – Baghdad , were 120(48%) at age (26-30) years old ,125 (41.6%) with primary education .